2012
DOI: 10.1073/pnas.1213021110
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1 promotes malignant progenitor reprogramming in chronic myeloid leukemia

Abstract: The molecular etiology of human progenitor reprogramming into self-renewing leukemia stem cells (LSC) has remained elusive. Although DNA sequencing has uncovered spliceosome gene mutations that promote alternative splicing and portend leukemic transformation, isoform diversity also may be generated by RNA editing mediated by adenosine deaminase acting on RNA (ADAR) enzymes that regulate stem cell maintenance. In this study, wholetranscriptome sequencing of normal, chronic phase, and serially transplantable bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
200
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(207 citation statements)
references
References 49 publications
7
200
0
Order By: Relevance
“…Like AS, mRNA editing is known to contribute to a variety of mammalian phenotypes (Jiang et al 2013). However, to the best of our knowledge, the genetic basis and variability of mRNA editing in genetically diverse individuals is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Like AS, mRNA editing is known to contribute to a variety of mammalian phenotypes (Jiang et al 2013). However, to the best of our knowledge, the genetic basis and variability of mRNA editing in genetically diverse individuals is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ADAR plays a major role in chronic myeloid leukemia (CML) tumor progression. In these studies, most cells underwent apoptosis following ADAR reduction (Steinman et al 2012;Jiang et al 2013). We used RT-PCR in order to verify AS of HNRNPR in HepG2 ADAR KD cells (Supplement 1, Supplemental Fig.…”
Section: Cells and Transfectionsmentioning
confidence: 99%
“…Sequencing analysis of BC LSCs revealed GSK3β missplicing (16), ADAR1 RNA editase activation (17), and BCL2 splice isoform switching (18). Although similarities between hESC and LSC transcriptional programs had previously been reported in a mouse model of AML, embryonic splice isoform patterns were not examined (19,20).…”
mentioning
confidence: 99%